The accuracy level of shooting using the instep and inside foot among extracurricular football students - Muhammad Fitra Ramadani; Rices Jatra (Journal of Applied Movement and Sport Science, 2025)
Background Shooting accuracy is a fundamental skill in football, directly influencing scoring opportunities and overall game performance. Observations during training sessions of the extracurricular football program at SMK Negeri 4 Pekanbaru indicated that many students struggled to execute accurate shots using both the instep and inside foot, often missing the intended target. Such technical inconsistencies can hinder the development of optimal performance in competitive play. Objectives This study aimed to evaluate the accuracy level of shooting using the instep and inside foot among extracurricular football students at SMK Negeri 4 Pekanbaru. Methods A descriptive quantitative research design was employed, with a sample of 20 students selected from the program. The data were collected using a standardized shooting test incorporating both techniques. Each student’s performance was assessed, and scores were averaged and categorized according to established criteria Results The analysis revealed that the combined average score for shooting accuracy using the two techniques was 18.93, which falls into the “fair” category. These results suggest that while students possess basic competence in shooting, there remains substantial room for improvement in precision and consistency. Conclusion In conclusion, the overall shooting accuracy among the participants is at a fair level, highlighting the need for targeted skill-based training to enhance both instep and inside foot shooting techniques. This study contributes to school football coaching strategies by providing baseline data to design more focused, technique-specific training interventions aimed at improving performance in extracurricular football programs.